Q: In the math equation 3x what is 3?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

3x times x is the same as 3x times 1x seeing that x has the same value its basically 3times 1 but don't forget the x so 3x Another way is to take out the x from 3 and 1 x(3*1) = x(3) =3x

It is a straight line equation as for example when y = 3x+6 then 3 is the slope and 6 is the y intercept.

You have one equation in two unknowns. There is no solution possible without a second (independent) equation in the same two unknowns.

3 is the coefficient of x and 3x means 3 times x which on its own is not an equation because there is no equality sign .

That type of math problem is called an algebraic equation.

Related questions

The mathematical phrase "6x" is not an equation. It is simply an expression. In math, an expression is a term or terms like 5 or 3x + 2. An equation must show an expression's relationship to another: 5x + 3 = 4 3 + 2 = 5

3x times x is the same as 3x times 1x seeing that x has the same value its basically 3times 1 but don't forget the x so 3x Another way is to take out the x from 3 and 1 x(3*1) = x(3) =3x

If the equation is (2x)^3-3x, then the answer is -985. However, if the equation if 2(x)^3-3x, then the answer is -235.

It is a straight line equation as for example when y = 3x+6 then 3 is the slope and 6 is the y intercept.

3x+4=10 To solve: 3x+4=10 3x=6 x=2

You have one equation in two unknowns. There is no solution possible without a second (independent) equation in the same two unknowns.

3 is the coefficient of x and 3x means 3 times x which on its own is not an equation because there is no equality sign .

Known equation: 3x+5y = 6 or y = -3/5x +6/5 Slope of equation: -3/5 Slope of parallel equation: -3/5 Parallel equation: y-1 = -3/5(x-3) => 5y = -3x+14 Parallel equation in its general form: 3x+5y-14 = 0

From first equation, -y = 3x + 3. Substitute in second equation: -3x + 5(3x + 3) = -21 ie 12x = -36 so x = -3 and y = -(-9 + 3) = 6. Easier method: subtract first equation from second giving -4y = -24 so y = 6, this in first equation gives -6 = 3x + 3, ie 3x = -9 so x = -3

That type of math problem is called an algebraic equation.

The equation 3X take away 11 times 2 equals -2. This is algebra math problem.

The equation 3X take away 11 times 2 equals -2. This is algebra math problem.